Pengaruh Lidah Buaya Menurunkan Kadar Glukosa Darah pada Diabetes Melitus Tipe 2 - Hezby Aziz El Qahar (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Background: The management of diabetes involves the medical treatment, including pharmacotherapy or anti-diabetic drugs as management. Diabetes Mellitus Type 2. Pharmacotherapy drugs in their use are often accompanied by side effects on the human body, therefore, various kinds of complementary treatments are studied to find ingredients that can be used as anti-diabetic, one of the phyto-pharmacy that is believed to have an anti-diabetic effect is aloe vera (Aloe vera). Aim: To determine the effect of aloe vera (Aloe vera) to reduce blood glucose levels in type 2 diabetes mellitus. Methods: The method used by the author is a literature study from various national and international journals. This method is used with the aim of presenting, increasing knowledge and understanding of the topics discussed by summarizing the material that has been published and providing factual information or new analysis from the relevant literature review and then comparing the results in the article. Results: Aloe vera contains chemicals that have hypoglycemic properties including chromium, alprogene, acemannan, anthraquinone, phytosterol, and methanol. Conclusion: Aloe vera has been shown to reduce blood glucose levels in type 2 diabetes mellitus.